2012
DOI: 10.1016/j.nutres.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ingestion and exercise training improve vascular endothelial function in postmenopausal women

Abstract: Vascular endothelial function is declines with aging and is associated with an increased risk of cardiovascular disease. Lifestyle modification, particularly aerobic exercise and dietary adjustment, has a favorable effect on vascular aging. Curcumin is a major component of turmeric with known anti-inflammatory and anti-oxidative effects. We investigated the effects of curcumin ingestion and aerobic exercise training on flow-mediated dilation as an indicator endothelial function in postmenopausal women. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 31 publications
5
95
0
Order By: Relevance
“…Some clinical studies showed that BCM-95 had beneficial effects on patients with rheumatoid arthritis (RA) (40) and oral submucous fi brosis (OSMF) (41). Theracurmin was reported to be able to potentially improve the age-related decline in endothelial function (26) and systolic blood pressure (27) in postmenopausal women. These studies showed not only the effi cacy but also the long-term safety of these DDS curcumin formulations in humans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some clinical studies showed that BCM-95 had beneficial effects on patients with rheumatoid arthritis (RA) (40) and oral submucous fi brosis (OSMF) (41). Theracurmin was reported to be able to potentially improve the age-related decline in endothelial function (26) and systolic blood pressure (27) in postmenopausal women. These studies showed not only the effi cacy but also the long-term safety of these DDS curcumin formulations in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The total curcumin content in each preparation was considered to be approximately equal without breaking the capsules. Theracurmin was reported to be used at 100-400 mg in patients with cancer or healthy elderly volunteers for chronic treatment in clinical studies, indicating that at least 400 mg of Theracurmin was safe (24)(25)(26)(27). Moreover, more than 10 phase 2 clinical trials are now ongoing using 180 mg of Theracurmin, and no signifi cant adverse effect has been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26) Furthermore, the promising efficacy of curcumin has been demonstrated across a variety of medical fields, in preclinical studies and in human clinical trials, using the highly bioavailable formulation of curcumin, Theracurmin ÂŽ . [27][28][29][30][31][32][33][34][35][36] In general, once they are absorbed into the body, polyphenols are mainly conjugated with glucuronic acid or sulfuric acid in the liver, with some excreted into the duodenum with bile, and some released into the blood. It is thought that the metabolites excreted into the duodenum could be hydrolyzed back to the original compound by hydrolases including β-glucuronidase, and then reabsorbed through the intestinal tract, and returned to the liver through the portal vein via enterohepatic circulation.…”
mentioning
confidence: 99%